2014
DOI: 10.1016/j.ultsonch.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of diclofenac sodium using combined processes based on hydrodynamic cavitation and heterogeneous photocatalysis

Abstract: Diclofenac sodium, a widely detected pharmaceutical drug in wastewater samples, has been selected as a model pollutant for degradation using novel combined approach of hydrodynamic cavitation and heterogeneous photocatalysis. A slit venturi has been used as cavitating device in the hydrodynamic cavitation reactor. The effect of various operating parameters such as inlet fluid pressure (2-4 bar) and initial pH of the solution (4-7.5) on the extent of degradation have been studied. The maximum extent of degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(64 citation statements)
references
References 42 publications
2
55
0
7
Order By: Relevance
“…Several researchers reported that reaction rate increased up to certain upstream pressure. Bagal and Gogate (2014) reported reaction rate was decreased at 4 bar due to degradation reaction and Vichare et al (2000) reported decomposition reaction started at 3.8 bar. Therefore, an optimised inlet pressure of 3 bar was selected for further work.…”
Section: Resultsmentioning
confidence: 96%
“…Several researchers reported that reaction rate increased up to certain upstream pressure. Bagal and Gogate (2014) reported reaction rate was decreased at 4 bar due to degradation reaction and Vichare et al (2000) reported decomposition reaction started at 3.8 bar. Therefore, an optimised inlet pressure of 3 bar was selected for further work.…”
Section: Resultsmentioning
confidence: 96%
“…It is also noted that large bubbles and cracks that appear in the degraded membrane which may be due to the heat and gases released from Fenton's reagent reaction [56], and which may also lead to expansion of the water channels. This is illustrated, cartoon-fashion in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, novel advanced treatment processes have also been reported for removal of diclofenac sodium [11,12]. These techniques possess various disadvantages such as slower removal kinetics as well as high operational costs along with hazardous byproducts including 5-hydroxydiclofenac and diclofenac-2,5-iminoquinone in ozonebased methods [10].…”
Section: Introductionmentioning
confidence: 99%